2010
DOI: 10.1088/0022-3727/44/2/022001
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-thermal transient plasma for enhanced flame ignition in C2H4–air

Abstract: Transient plasma ignition, involving short ignition pulses (typically 10–50 ns), has been shown to effectively reduce ignition delays and improve engine performance for a wide range of combustion-driven engines relative to conventional spark ignition. This methodology is therefore potentially useful for many engine applications; however, at present there is limited understanding of the underlying physics. Evidence is presented here for two distinct phases of the plasma-ignition process: an initial non-equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(68 citation statements)
references
References 22 publications
0
68
0
Order By: Relevance
“…Shown here are streamers generated by a 54 ns, 61 kV pulse across a 15 mm gap [4]. Production of active particles in streamer channels through electron impact dissociation, excitation, and ionization of atoms and molecules significantly impact chain branching reactions, reducing ignition delay times and allowing for more complete combustion.…”
Section: Transient Plasma Ignitionmentioning
confidence: 99%
“…Shown here are streamers generated by a 54 ns, 61 kV pulse across a 15 mm gap [4]. Production of active particles in streamer channels through electron impact dissociation, excitation, and ionization of atoms and molecules significantly impact chain branching reactions, reducing ignition delay times and allowing for more complete combustion.…”
Section: Transient Plasma Ignitionmentioning
confidence: 99%
“…Left: streamers generated by a single 370 mJ, 56 kV, 54 ns pulse (maximum E/n ≈ 400 Td) in air (10 s gate time); Right: flame propagation from multiple ignition sites at the base of the streamers after a single pulse in φ = 1.1 C 2 H 4 -air mixture (1 ms gate time). Both images were captured from the same off-axis angle [Singleton et al, 2011].…”
Section: Ignition Control In Quiescent Gasmentioning
confidence: 99%
“…Two distinct phases of the plasma-ignition process were demonstrated in [Singleton et al, 2011]: an initial non-equilibrium plasma phase, wherein energetic electrons transfer energy into electronically excited species that accelerate reaction rates, and a spatially distributed thermal phase, that produces exothermic fuel oxidation reactions that result in ignition. It is shown that ignition kernels are formed at the ends of the spatially separated streamer channels, at the cathode and/or anode depending on the local electric field strength, and that the temperature in the streamer channel is close to room temperature up to 100 ns after the discharge [Singleton et al, 2011]. The results presented in Figure 10 show that after a transient plasma discharge in a φ = 1.1 C 2 H 4 -air mixture at 1 atm, (i) ignition occurred within the streamer channel, (ii) flame initiation occurred within 1 ms of the discharge and (iii) flame propagation was faster than that initiated by conventional spark ignition.…”
Section: Ignition Control In Quiescent Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent approach to reducing ignition delay is ignition using transient, non-equilibrium plasmas. This method has proven to be more efficient compared to traditional spark ignition, [3][4][5] which uses a thermal form of plasma to create a pocket of hot gas to initiate combustion. In the case of non-equilibrium plasma ignition, a nanosecond-scale electrical discharge results in atoms and molecules that are excited to higher electronic, vibrational, and rotational states in which they remain for a few tens or hundreds of nanoseconds.…”
Section: Introductionmentioning
confidence: 99%